Value-based leadership in turbulent times: Lessons from the Corona crisis and recommendations for post-pandemic management in the health sector - Maximilian C. von Eiff; Wilfried von Eiff; Mohamed Ghanem (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
The Corona crisis not only exposed the causes of supply disruptions for system-critical medical products and pharmaceuticals, and made the consequences of the digitalization gap in the health care system transparent, but in particular, revealed the consequences of fundamental leadership deficits in hospital personnel management, professional profiles and ethics, professional policies, and procurement management. However, Corona has also triggered a rethinking of the values, meaning and purpose of work content and behavioral norms. This paper aims to identify and analyse management failures observed and experiences made during the Corona pandemic. Based on these findings recommendations for good leadership practices are given. By literature research reported experiences from physicians and nurses were analysed related to working conditions, motivation-to-work, and satisfaction with incentive systems. Furthermore, interviews with clinical staff working under Corona conditions were realised based on a structured questionnaire. The workload of nursing has increased significantly due to economization: from 2005 to 2017, the number of treatment cases increased by 12%, while at the same time, the number of beds decreased by 9.4% and the length of stay shortened from 8.4 to 7.3 days. The accumulated nursing overtime in German hospitals alone is equivalent to 17,800 full-time employees. During the Corona crisis the working situation especially for nurses facilitating patients ventilated on the intensive care unit has dramatically worsened: additional overtime, high patient mortality, resource-intensive and stressful care requirements lead to prostration and mental exhaustion. As a consequence of this tremendous work burden for nurses and physicians during the Corona pandemic up to 30% of these occupational groups gave voice to inadequate working conditions and utter their intention to quit their jobs. Demotivation and a flight into professions remote from medicine are a reaction of many physicians and nurses to years of leadership failures in hospitals and politics, as well as an increasing economization of medicine. Between 68 and 82% of physicians cite the cost pressure associated with rationing as a source of dissatisfaction with their professional situation. It is up to management to learn from these findings, implement the necessary measures and provide family-friendly working conditions for occupational groups working "at the bed-side". A "value-based leadership model" that takes into account the specific conditions prevailing in the healthcare industry was developed and serves as a compass in meeting and overcoming this challenge. This paper transfers practical experiences made during the Corona pandemic and pertaining to motivation-to-work under stressful working conditions, the meaning of "purpose", the try-out of so far unknown working practices and types of inter-occupational co-operation into a leadership model that is unique for the health care sector.
Keywords: 330; Corona crisis; Digitalization; Economies of scale; Economization of medicine; Purpose; Supply shortages; Working conditions "at the bedside"